EFL STUDENTS’ PREFERENCE IN RECEIVING WRITTEN CORRECTIVE FEEDBACK (Universitas Kuningan, 2019)
One solution to help EFL (English as a Foreign Language) students in writing skill is providing a written corrective feedback by a teacher. Somehow, it is also necessary for a teacher to know the appropriate feedback given to their students. This study had two purposes: 1) To describe the students’ thought toward feedback strategies with different proficiency levels in general and in specific writing aspects content; and 2) To explore the most students’ preference with different proficiency levels in general and in specific writing aspects content and form. A qualitative data analysis approach was integrated using an interview, eight students in total were chosen to be interviewed; two from each group and level (two-high, two low direct feedback with an end note and two-high, two-low indirect feedback with an end note). N vivo was used to analyze the content analysis of the data. The study found that no matter low or high proficient writers, they had a positive attitude toward the teacher’s feedback and most of them preferred to receive direct corrective feedback to improve their writing performance both in content and form. In brief, providing a feedback is needed for students however it must be advisable with students’ proficiency level in order to make them easier in understanding the feedback.